Progressive Muscle Relaxation Technique In Type 2 DM Patients With Unstable Blood Glucose Levels: Case Report: Teknik Relaksasi Otot Progresif Pada Pasien DM Tipe 2 Dengan Ketidakstabilan Kadar Glukosa Darah : Case Report - Anggun Dwi Putri, Anggun; Nova yanti, Nova; Netti; Suhaimi (Journal of Health and Cardiovascular Nursing, 2023)
Diabetes mellitus is a collection of symptoms in a person caused by an increase in blood glucose levels due to decreased insulin secretion. To overcome the instability of blood glucose levels can be through two ways, namely pharmacological and non-pharmacological therapies. One of the non-pharmacological techniques is relaxation that can stabilize blood glucose levels, the type of relaxation therapy that has high effectiveness in reducing blood sugar levels is progressive muscle relaxation therapy. This research design is a type of descriptive observational research in the form of a case report. The research time was from May 15 to June 3, 2023. The population of this study were all male patients with DM who were admitted to the Interne room in Padang Hospital. The sample amounted to 2 people taken by purposive sampling technique. Data collection techniques using interview methods, physical examination and observation of DM patients with blood sugar checks for the application of progressive muscle relaxation therapy to stabilize blood glucose levels. The evaluation results of the intervention given to patients showed the effect of progressive muscle relaxation therapy in stabilizing the blood glucose levels of Diabetes Mellitus patients in the Male Interne room of in Hospital.  The suggestion of this study is that progressive muscle relaxation techniques can be considered to be an alternative non-pharmacological intervention that can be done by nurses to reduce blood glucose levels of patients with Type 2 DM.